Porous Electrocatalysts: Hierarchically Structured Ultraporous Iridium‐Based Materials: A Novel Catalyst Architecture for Proton Exchange Membrane Water Electrolyzers (Adv. Energy Mater. 4/2019). Issue 4 (24th January 2019) - Faustini, Marco; Giraud, Marion; Jones, Deborah; Rozière, Jacques; Dupont, Marc; Porter, Thomas R.; Nowak, Sophie; Bahri, Mounib; Ersen, Ovidiu; Sanchez, Clément; Boissière, Cédric; Tard, Cédric; et al.
Abstract : In article number1802136 Cédric Boissière, Cédric Tard, Jennifer Peron and co‐workers present the synthesis of ultra porous nanostructured iridium‐based microspheres using a cheap and easily scalable water‐based process. These hierarchical catalysts are active and stable towards the oxygen evolution reaction. They are easily processed to make percolated and highly porous anode catalyst layers that are ideal for gas, water, proton and electrons transport when integrated into the proton exchange membrane of electrolysis cells.